2020
DOI: 10.1111/ecc.13216
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition guidance for cancer patients and survivors—A review of the websites of Irish healthcare and charitable organisations and cancer centres

Abstract: Objective To determine availability of nutrition information for cancer patients and survivors from Irish healthcare organisations, cancer charity and support groups and assess its quality and readability. Design Cross‐sectional. Setting The National Health Service Executive websites were searched, as were the sites of the ten largest cancer charities/support groups identified through the Benefacts website. An additional internet search was conducted to ensure no large organisations/support groups were missed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…We identified a lack of details regarding high protein or high calorie intake to make specific dietary recommendations, and there was no guidance on the long-term consumption of high protein or high calorie foods. The same gap was also identified by authors that explored information available in English-speaking countries [ 38 , 47 ]. However, counseling with a dietitian or healthcare professional was always recommended for personalized planning care.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We identified a lack of details regarding high protein or high calorie intake to make specific dietary recommendations, and there was no guidance on the long-term consumption of high protein or high calorie foods. The same gap was also identified by authors that explored information available in English-speaking countries [ 38 , 47 ]. However, counseling with a dietitian or healthcare professional was always recommended for personalized planning care.…”
Section: Discussionmentioning
confidence: 55%
“…Similar studies for English-speaking countries [ 38 , 47 ] have suggested that cancer websites should consider a specific online platform to provide more focused information on nutrition, due to the great variety of nutritional needs during cancer. In this approach, our website ( accessed on 30 October 2021) presents an important step forward to bridge this gap.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A 2020 study reported that only 15% of healthcare organisations, cancer charities and support groups provided nutrition guidance for cancer patients, whereas just 9.3% provided guidance for cancer survivors. 20 This is echoed by the findings of de Kruif et al 19 who reported that breast cancer patients undergoing chemotherapy experienced little dietary support from HCPs during treatment despite this treatment often negatively impacting dietary intake, with those reporting poorer intake experiencing more fatigue and perceiving less opportunities to be physically active. Research shows that cancer diagnosis alone is not sufficient to bring about changes to dietary intake, therefore highlighting the role of intervention to facilitate change.…”
Section: Discussionmentioning
confidence: 98%
“…Risk assessment and counseling of patients on the prevention of BC is highly dependent on the oncology provider. Patients with cancer strongly prefer to receive information about physical activity, diet, and weight management from their oncology providers ( 133 ). Studies indicate that oncology providers play a pivotal role and their sessions with patients are very influential ( 50 , 134 , 135 ), which leads to increased physical activity among cancer survivors ( 136 , 137 ).…”
Section: Role Of Oncology Providermentioning
confidence: 99%